Large Enhancements in Southern Hemisphere Satellite‐Observed Trace Gases Due to the 2019/2020 Australian Wildfires. Issue 18 (13th September 2021) - Pope, Richard J.; Kerridge, Brian J.; Siddans, Richard; Latter, Barry G.; Chipperfield, Martyn P.; Arnold, Stephen R.; Ventress, Lucy J.; Pimlott, Matilda A.; Graham, Ailish M.; Knappett, Diane S.; Rigby, Richard
Abstract: The 2019/2020 Australian wildfires emitted large quantities of atmospheric pollutant gases and aerosols. Using state‐of‐the‐art near‐real‐time satellite measurements of tropospheric composition, we present an analysis of several emitted trace gases and their long‐range transport, and compare to the previous (2018/2019) fire season. Observations of carbon monoxide (CO) show that fire emissions were so intense that the distinct Australian fire plume managed to circumnavigate the Southern Hemisphere (SH) within a few weeks, with eastward propagation over the South Pacific, South America, the South Atlantic, Africa, and the Indian Ocean. Elevated atmospheric methane levels were also detected in January 2020 fire plumes over the Pacific, defined using CO as a plume tracer, even though sampling was restricted spatially by aerosols and clouds. Observations also show significant enhancements of methanol (CH3 OH) from the fires, where CH3 OH:CO enhancement ratios increased within the aged plume downwind over the South Pacific indicating secondary in‐plume CH3 OH formation. Plain Language Summary: The 2019/2020 Australian wildfires emitted large quantities of smoke and gaseous pollutants. Using satellite observations, we analyze the long‐range transport of several trace gases and compare with the previous (2018/2019) fire season. The 2019/20 fires were so intense that a distinct plume of carbon monoxide was observed to propagate around the entire Southern Hemisphere in just a few weeks. Enhancement of methane was also detected in the plume along with substantial quantities of methanol. The ratio between methanol and carbon monoxide increased over the Southern Pacific suggesting the secondary formation of methanol within the fire plume as it propagated eastwards. Key Points: Satellite‐retrieved carbon monoxide (CO) plumes from the Australian fires circumvent the Southern Hemisphere Satellite‐retrieved methanol (CH3 OH) shows downwind enhancement of CH3 OH:CO ratio suggesting in‐plume secondary CH3 OH production as well as direct emission Substantial enhancements in methane (CH4 ) are detected from space